ANALISIS MOTIVASI, BUDAYA ORGANISASI DAN KINERJA - Yuliana Dwi Endah Arumsari; Siska Wulandari; Nur Wening (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study was to analyze motivation, organizational culture and performance. This research is conducted in Community and Village Empowerment Office, it used sample of 33 ASN consist of Office Secretary, Head of Section, Head of Subdivision, Section Head and Staff, data is collected using questioners. This research is to analyze motivational variable data, organizational culture and performance using quantitative descriptive analysis. Data is divided into primer data and secondary data. The scoring of this research uses a Likert scale. To describe the figure of each variable studied, the data is tabulated and uses a statistical descriptive analysis by calculating the mean (mean). The analysis result present that variable motivation of State Civil Apparatus in the Office of Community Empowerment and Village of Sleman Regency generally get a good category with mean 3,79. While organizational culture variables generally also get a good category with mean 3,83. The ASN Performance variable in the Community and Village Empowerment Service, although it is not yet maximal, it also has a good category with mean 3, 49. Even though the performance variable obtains the lowest mean compared to the motivation variable and organizational culture variable, it remains in the good category. Keywords: Motivation, Organizational Culture, Performance